2014
DOI: 10.1109/jsen.2013.2296155
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biosensor Based on Silver-Enhanced Self-Assembled Radio-Frequency Antennas

Abstract: In this letter, we show that a silver-enhancement technique can be used to self-assemble a radio-frequency (RF) antenna, which then can be used for designing a radio-frequency identification (RFID)-based biosensor. Using the proposed biosensor, the concentration of target analytes or pathogens can be remotely interrogated in a concealed, packaged, or in a biohazardous environment, where direct measurement is considered to be impractical. In the presence of the target analytes or pathogens, a silver-enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…The time response to collect and display the sensing results on the Android smartphone application was less than 1 s. RFID tag sensors have been used for food safety. Yuan et al 242 reported a silver-enhancement method usable for selfassembling a chain of micromonopole RF antennas. The RFIDbased biosensor detected the rabbit IgG within 20 to 60 ng concentrations where a reected RF signal was received at the 915 MHz RFID reader.…”
Section: Silver Nanoparticle-based Rfid Tag Sensorsmentioning
confidence: 99%
“…The time response to collect and display the sensing results on the Android smartphone application was less than 1 s. RFID tag sensors have been used for food safety. Yuan et al 242 reported a silver-enhancement method usable for selfassembling a chain of micromonopole RF antennas. The RFIDbased biosensor detected the rabbit IgG within 20 to 60 ng concentrations where a reected RF signal was received at the 915 MHz RFID reader.…”
Section: Silver Nanoparticle-based Rfid Tag Sensorsmentioning
confidence: 99%
“…Inductors are widely used to integrate with capacitors to construct inductor-capacitor (LC) or inductor-capacitor-resistor (LCR) circuits as the sensing devices [ 22 , 59 , 60 ], and the construction of the entire device structure is simple and straightforward. Dipole antennas have also been studied for wireless transmission of sensing signals [ 57 , 61 ].…”
Section: Wireless Rfid-based Biological Electronic Sensorsmentioning
confidence: 99%
“…In [10], we had proposed an alternative concept for implementing a RFID based biosensor. Based on the presence of different concentration levels of target analytes, the structure of the antenna changes leading to the change in the antenna's reflection properties.…”
Section: Introductionmentioning
confidence: 99%
“…An example of printable tags/sensors are the RFID based humidity sensor reported in [11] which used silver-ink deposited on polymide films. In this paper, we extend the concept proposed in [10] to characterize and optimize the parameters of the sensor using multi-physics finite-element simulations. Also, in this paper we have explored a new application of the self-assembly based sensing that is for detection of moisture/humidity.…”
Section: Introductionmentioning
confidence: 99%